(3GdQSGdI GdhdOjIs - (3GdeQYTj, SGLbdj RGOg, eMeO Hf CHi HcQ, J(B1145(3g`s
(3ChdgG (B:s
(3HSe Gddg hHMeOg hSdGe Ydi QSdg gPg QSGdI aj af GdefGXQI YedJgG dc jG hdO hdCeKGdc GdeHJOFjf HGQc Gddg ajgG dc hdef CQGO ZjQc hgPG daf dG Tc aj GSJMHGH JMUjdg hEfeG GdTc aj hLhHg (B...s
(3BNQgG (B:s
... (3ajHbi eOYj GdeYdd HdG Odjd adjS MGUd GdeYGQVI GHWGd OYhi GdeYdd aCbhi GdGYJQGVGJ GHWGd GdeOYj GdZjQ GdeOdd HOdjd hEf Sei Pdc ZUHG hCSdegG GdefY Cf dG jLH dg SfO (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\60s
(3gOjI GdYGQajf (B2/322s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs